Limitations and perspectives of the novel salivary test for endometriosis: an open web-based survey study of German gynecologic healthcare providers - Nigdelis, Meletios P.; Doerk, Merle; Burghaus, Stefanie; Sillem, Martin; Hamoud, Bashar Haj; Solomayer, Erich Franz; Olmes, Gregor Leonhard (Archives of Gynecology and Obstetrics, 2024)
Introduction: The description of a salivary miRNA signature for endometriosis has led to the development of a non-invasive diagnostic test. Current healthcare provider practices regarding the test remain uncaptured. The application of this test in practice was examined in a web-based survey, with the aim to provide their opinions on it. Methods: We conducted an open web-based survey study between November 2023 and January 2024. Members of the German society of gynecologic endoscopy (Arbeitsgemeinschaft gynäkologische Endoskopie, AGE), society of endometriosis (Arbeitsgemeinschaft Endometriose, AGEM), and the endometriosis research foundation (Stiftung Endometriose Forschung, SEF) were contacted per e-mail twice. Participants’ data were anonymized. Differences in responses based on self-reported expertise in the field (basic knowledge, specialized knowledge, expert) were assessed using the χ2-test or Fisher’s exact test. Statistical significance was set as p < 0.05. Results: In total 141 of 190 respondents completely responded to the survey (> 75% of the questions of the survey). Twenty-one physicians reported having experience with the test, while most participants had at least specialized knowledge on the field (112/141). In terms of specific questions, more than 90% found the costs high; almost 85% did not believe that the test replaces standard diagnostic tools (histology, clinical examination, and sonography). Eighty-six providers supported the use of the test in adolescents. Gynecologists with basic knowledge had a more positive attitude compared with more experienced ones in terms of usefulness (Fisher’s exact test, p < 0.001). Significant differences were demonstrated between expertise groups regarding (not only) applicability in adolescents (Fisher’s exact test, p = 0.004), and using the test for screening purposes (χ2-test, p = 0.002). Discussion: Despite the promising benefits of a salivary test for endometriosis, German healthcare providers would not change current practices. Nevertheless, less experienced colleagues were more positive towards the test.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Endometriosis; miRNA; Non-invasive diagnosis; Salivary test